Northern Alberta : map showing disposition of lands - Lynch, F. C. C. (Francis Christopher Chisholm), 1884- (Department of the Interior Canada, 1928)
This is a map of Northern Alberta in 1928 showing vacant surveyed Dominion lands, forest reserves, First Nations reserves, parks, timber berths and grazing leases, railroads, cities and towns. It includes notes on soil type and quality, vegetation and relief. Fourteenth edition. Scale 1:792,000, or 12.5 miles to 1 inch. Relief shown by spot heights and relief notes. Includes notes on soil type and quality, vegetation and relief. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows vacant surveyed Dominion lands, forest reserves, First Nations reserves, parks, timber berths and grazing leases, railroads, cities and towns.